Ethical dilemmas associated wih hyper-structured student research - Steyn, R. (South African Journal of Higher Education, 2020)
The growth in the number of students engaging in research as part of their studies has increased dramatically, and combined with the need to provide adequate research supervision, the exploration and development of alternative modes of conducting research together with students has emerged. One such mode of research can be called the hyper-structured student research project (HSSRP). This mode represents supervision where the research area, as well as the methodology, is specifically defined, and where students are supported and guided through every step of the research process, with the supervisor making most of the important research decisions on behalf of the students. Although the HSSRP has delivered on the institutional requirements of efficiency and throughput, there is a need to critically reflect on these projects to ascertain whether they meet academic and professional requirements. In this paper, the acceptability of HSSRP projects will be analysed from a utilitarian perspective, considering dilemmas that may arise from, but also within, the projects, and focusing on the public worth which follows from such projects. Several new insights arose from these analyses, and it was found that the level of public worth might be less than when more traditional modes of supervision is used. It may be concluded that the higher level outcomes, such as graduateness and professional preparedness, are not achieved through the HSSRP. This paper presents an evaluation of the HSSRP from a multi-dimensional utility perspective and contributes to a debate often driven by biased and limited utilitarianism. It is recommended that the critique expressed in this paper be used to design structured research projects so as to enable a more even distribution of utility and to enable universities to deliver on their societal higher goals.